The production of knowledge about graduates in field education in Brazil (2007 – 2022) (Revista Contexto & Educação, 2026)
This study aimed to inventory the production of knowledge about Degrees in Rural Education in Brazil, considering the period from 2007 to 2022. As an investigative problem, it highlighted: how the production of knowledge about Degrees in Rural Education in Brazil has been developing, in theses and dissertations, from 2007 to 2022? To produce the data, we used a bibliographic survey carried out in the CAPES Catalog of Theses and Dissertations. 129 theses and dissertations were analyzed, with emphasis on the territorial distribution of productions, investigative themes, the evolution of studies, among others. It was concluded, among other aspects, that the academic production listed is significant, considering the length of time this type of degree has existed in Brazil.
Keywords: Degrees in Rural Education; Rural Education; Teacher Training